HOMONYMOUS PSYCHOLOGICAL TERMS IN UZBEK AND ENGLISH LANGUAGES (TAMADDUN NURI JURNALI, 2025)
Homonymy is a linguistic phenomenon where two or more words have the same spelling or pronunciation but different meanings. This article studies the features of homonymy between psychological terms in Uzbek and English languages.